Highly Enantioselective Michael Addition of Malonates to β‐CF3‐β‐(3‐Indolyl)nitroalkenes: Construction of Trifluoromethylated All‐Carbon Quaternary Stereogenic Centres. Issue 19 (23rd May 2014) - Ma, Chun‐Hui; Kang, Tai‐Ran; He, Long; Liu, Quan‐Zhong
Abstract: A family of γ‐nitrobutyric acid esters bearing an all‐carbon quaternary stereogenic centre have been synthesized. Chiral thioureas catalysed the conjugate addition of malonates to nitroalkenes containing a trifluoromethyl and indole motif at the β‐position to afford the corresponding γ‐nitrobutyric acid esters in good yields (up to 89 % yield) and with good to excellent enantioselectivities (up to 90 % ee ). This protocol provides an efficient access to optically enriched γ‐amino acids and β‐disubstituted γ‐butyrolactams. Abstract : Trifluoromethylated all‐carbon quaternary stereogenic nitroalkanes have been synthesized in good yields and with good to excellent enantioselectivities by organocatalysed asymmetric Michael addition of malonates to nitroalkenes containing a trifluoromethyl and indole motif. This protocol provides an efficient access to optically enriched γ‐amino acids and β‐disubstituted γ‐butyrolactams.